Pie crusting of ligaments - Wong, Zoe Sher Mun (Nanyang Technological University, 2022)
Total knee arthroplasty is a surgical technique for patients with significant meniscus tears and osteoarthritis. Pie-crusting of the ligaments may be required in some circumstances. Pie-crusting is a surgical procedure performed by making several incisions in ligaments and tendons with the goal of lengthening the ligament or tendon. This is done mostly on the lateral collateral ligament, but access to the medial side of the knee is required for the treatment of varus knees. There is currently insufficient information about the effect of pie-crusting on the medial collateral ligament (MCL). As a result, the goal of this research is to see how pie-crusting affects the MCL's biomechanical properties.